(untitled) (Baltic Journal of Sport and Health Sciences, 2011)
Research background and hypothesis. Traditional time series analysis techniques, which are also used for the analysis of cardiovascular signals, do not reveal the relationship between the changes in the indices recorded associated with the multiscale and chaotic structure of the tested object, which allows establishing short-and long- term structural and functional changes. Research aim was to reveal the dynamical peculiarities of interactions of cardiovascular system indices while evaluating the functional state of track-and-field athletes and Greco-Roman wrestlers. Research methods. Twenty two subjects participated in the study, their average age of 23.5 ± 1.7 years. During the study standard 12 lead electrocardiograms (ECG) were recorded. The following ECG parameters were used in the study: duration of RR interval taken from the II standard lead, duration of QRS complex, duration of JT interval and amplitude of ST segment taken from the V standard lead. Research results. Significant differences were found between inter-parametric connections of ST segment amplitude and JT interval duration at the pre and post-training testing. Observed changes at different hierarchical levels of the body systems revealed inadequate cardiac metabolic processes, leading to changes in the metabolic rate of the myocardium and reflected in the dynamics of all investigated interactions. Discussion and conclusions. It has been found that peculiarities of the interactions of ECG indices interactions show the exposure of the functional changes in the body at the onset of the workload. The alterations of the functional state of the body and the signs of fatigue, after athletes performed two high intensity training sessions per day, can be assessed using the approach of the evaluation of interactions between functional variables. Therefore the evaluation of the interactions of physiological signals by using time series analysis methods is suitable for the observation of these processes and the functional state of the body. Keywords: electrocardiogram, time series, functional state.